Epidemiology of retinal vein occlusions: state-of-the-art - L.K. Moshetova; S.А. Usharova; S.V. Simonova; K.I. Turkina (РМЖ "Клиническая офтальмология")
L.К. Moshetova1, S.А. Usharova1, S.V. Simonova1,2, К.I. Turkina1 1Russian Medical Academy of Continuous Professional Education, Moscow,  Russian Federation 2Research Institute of Public Health Organization and Medical Management,  Moscow, Russian Federation Impaired blood flow in various organs and tissues is a common cause of disabling disorders that even result in a lethal outcome. Despite an extremely rapid development of modern medicine, the rate of these disorders is still high thus emphasizing the importance of further detailed studies on this issue. In addition to systemic vascular diseases, local blood flow disturbances are also prevalent among population. These disturbances result from more significant blood flow disorders. Retinal vein occlusion is not an exclusion. Acute retinal vein occlusions account for more than half of ocular vascular diseases and may lead to extremely severe ophthalmic complications that result in poor vision, blindness, and reduced quality of life in both young and elderly patients. The diversity of clinical presentations, their severity, and clinical course make the diagnosis challenging thus altering the assessment of the prevalence of these diseases. Keywords: retinal vein occlusion, epidemiology, systemic vascular disorders, risk factors, retinal vessels. For citation: Moshetova L.К., Usharova S.А., Simonova S.V.,Turkina К.I. Epidemiology of retinal vein occlusions: state-of-the-art. Russian Journal of Clinical Ophthalmology. 2021;21(2):–89. DOI: 10.32364/2311-7729-2021-21-2-86-89.